Cadenas y eslabones del reciclaje: una aproximación etnográfica al trabajo con la basura - Rivadeneira, Catalina (2023)
This article makes a descriptive and analytical tour of the use of garbage in the city of Quito, using ethnography, it was observed through the recycling chain how social inequalities are producers of profitability in the links of this productive chain. The productive chain of recycling responds to the logic of accumulation of contemporary capitalism that takes advantage of the class and gender diversities of the lowest link in this chain to transform inequality for the benefit of the upper links. Thus, the super-exploitation and self-exploitation of poor women become essential to understand the profitability of this productive chain.